Conspicuous consumption and hospitality at a wine festival in China. Issue 2 (1st June 2019) - O'Regan, Michael; Choe, Jaeyeon; Yap, Matthew
The nature of Chinese consumption and hospitality has evolved rapidly since the post-1980s middle class adopted new lifestyles and consumption choices after the opening up of the economy and society. This study explores the logics underpinning conspicuous consumption of wine in China by way of an exploratory factor analysis of 253 respondents at a wine festival. The study found that conspicuous tendencies manifest themselves with wine consumption, but are affected by culture and traditional values. The study found that social and personal influences mediate how individuals perceive and experience consumption in ways that do not wholly follow western practices. This article contributes to the existing hospitality literature by conceptualizing from a consumer perspective, how a product or brand has the potential to become conspicuous within the Chinese hospitality context and explores implications for hospitality research by generating a thorough understanding of links between conspicuous consumption and hospitality.